Acylstannanes: Cleavable and Highly Reactive Photoinitiators for Radical Photopolymerization at Wavelengths above 500 nm with Excellent Photobleaching Behavior. Issue 37 (8th August 2018) - Mitterbauer, Moritz; Knaack, Patrick; Naumov, Sergej; Markovic, Marica; Ovsianikov, Alexandr; Moszner, Norbert; Liska, Robert
Abstract: Within this work, a novel acylstannane‐based photoinitiator (PI) is presented. Tetrakis(2, 4, 6‐trimethylbenzoyl)stannane (1 ) displays outstanding properties compared to state‐of‐the‐art acylgermane‐based initiators. Most importantly, the initiator shows absorption up to 550 nm, which allows higher penetration depths, especially in highly filled photopolymers. Besides that, 1 shows extremely high photoinitiating activity towards (meth)acrylic double bonds, as well as very fast photobleaching. Furthermore, unlike many organotin compounds, 1 shows surprisingly low cytotoxicity. Abstract : A new cure : A novel acylstannane‐based visible‐light photoinitiator, tetrakis(2, 4, 6‐trimethylbenzoyl)stannane (1 ), shows absorption at wavelengths up to 550 nm, which results in higher penetration depths, especially in highly filled photopolymers. Photoinitiator 1 also shows extremely high photoinitiating activity towards (meth)acrylic double bonds, very fast photobleaching and surprisingly low cytotoxicity.